Serine-Driven Metabolic Plasticity Drives Adaptive Resilience in Pancreatic Cancer Cells - Marcella Bonanomi; Sara Mallia; Mariafrancesca Scalise; Tecla Aramini; Federica Baldassari; Elisa Brivio; Federica Conte; Alessia Lo Dico; Matteo Bonas; Danilo Porro; Cesare Indiveri; Christian M. Metallo; et al. (Antioxidants)
Pancreatic cancer is one of the most lethal malignancies, in part due to its profound metabolic adaptability, which underlies drug resistance and therapeutic failure. This study explores the metabolic rewiring associated with resistance to treatment using a systems metabolomics approach. Exposure to the redox-disrupting agent erastin revealed key metabolic vulnerabilities but failed to produce lasting growth suppression. Combinatorial treatments with methotrexate or alpelisib significantly impaired proliferation and triggered marked metabolic shifts. Systems-level analyses identified serine metabolism as a central adaptive pathway in resilient cells. Metabolic tracing and gene expression profiling showed increased de novo serine biosynthesis and uptake, supporting redox homeostasis, biosynthetic activity, and epigenetic regulation. Notably, cells that resumed growth after drug withdrawal exhibited transcriptional reprogramming involving serine-driven pathways, along with elevated expression of genes linked to survival, proliferation, and migration. These findings establish serine metabolism as a functional biomarker of metabolic plasticity and adaptive resilience in pancreatic cancer, suggesting that targeting this adaptive axis may enhance therapeutic efficacy.